MANAJEMEN USAHA IKAN FUFU DI DESA TAMBALA KAMPUNG BARU KECAMATAN TOMBARIRI KABUPATEN MINAHASA PROVINSI SULAWESI UTARA - Rinaldi, Rian; Jusuf, Nurdin; Tambani, Grace O. (Universitas Sam Ratulangi, 2018)
AbstractIndonesian fisheries resources regarding food in the fisheries sector have great potential, this is an important factor in supporting national development.This study aims to determine the management of